Effects of Hyaluronic Acid and γ–Globulin Concentrations on the Frictional Response of Human Osteoarthritic Articular Cartilage - Park, Jae-Yong (PLoS One, 2014)
Synovial fluid plays an important role in lubricating synovial joints. Its main constituents are hyaluronic acid (HA) and γ–globulin, acting as boundary lubricants for articular cartilage. The aim of the study was to demonstrate the concentration-dependent effect of HA and γ–globulin on the boundary-lubricating ability of human osteoarthritis (OA) cartilage. Normal, early and advance stage articular cartilage samples were obtained from human femoral heads and in presence of either HA or γ–globulin, cartilage frictional coefficient (µ) was measured by atomic force microscopy (AFM). In advanced stage OA, the cartilage superficial layer was observed to be completely removed and the damaged cartilage surface showed a higher µ value (∼0.409) than the normal cartilage surface (∼0.119) in PBS. Adsorbed HA and γ–globulin molecules significantly improved the frictional behavior of advanced OA cartilage, while they were ineffective for normal and early OA cartilage. In advanced-stage OA, the concentration-dependent frictional response of articular cartilage was observed with γ–globulin, but not with HA. Our result suggested that HA and γ–globulin may play a significant role in improving frictional behavior of advanced OA cartilage. During early-stage OA, though HA and γ–globulin had no effect on improving frictional behavior of cartilage, however, they might contribute to disease modifying effects of synovial fluid as observed in clinical settings.